Tofacitinib Adherence and Outcomes in Refractory Inflammatory Bowel Disease. Issue 4 (23rd October 2021) - Wiles, C Alex; Shah, Nisha B; Bell, Jake; Pabla, Baldeep S; Scoville, Elizabeth A; Dalal, Robin L; Beaulieu, Dawn B; Schwartz, David A; Horst, Sara N
Abstract: Background: Tofacitinib has been approved for moderate-to-severe ulcerative colitis and studied in Crohn's disease. Understanding medication adherence to oral medications in severe disease is essential. Methods: We retrospectively reviewed adherence and real-world outcomes of inflammatory bowel disease patients who initiated tofacitinib at a single care center. Adherence was measured by proportion of days covered. Results: Sixty-three patients were identified. All patients failed at least one prior biologic therapy. Mean proportion of days covered was 95.7% for ulcerative colitis and 93.1% for Crohn's disease. Significant clinical and endoscopic response was seen. Conclusion: Adherence was high in a cohort with highly refractory disease. Lay Summary: Tofacitinib is the first oral medication approved for severe ulcerative colitis and has also been studied in Crohn's disease. In patients with severe and refractory inflammatory bowel disease, adherence to tofacitinib was high. Use of tofacitinib was safe and well-tolerated. Graphical Abstract: